Three dimensional hexagonal boron nitride nanosheet/carbon nanotube composites with light weight and enhanced microwave absorption performance. (September 2018) - Zhong, Bo; Cheng, Yuanjing; Wang, Meng; Bai, Yongqing; Huang, Xiaoxiao; Yu, Yuanlie; Wang, Huatao; Wen, Guangwu
Abstract: Three dimensional hexagonal boron nitride nanosheet decorated carbon nanotube composites (3D h -BNNS/CNTs) have been fabricated through a facile thermal treatment process. h -BNNSs randomly distribute among CNTs to form 3D network structure. The microwave absorption properties of these 3D h -BNNS/CNTs are obviously improved comparing with those of CNTs. And the minimum reflection loss (RL) can reach up to −36.5 dB when the absorber thickness is 2.5 mm for 3D h -BNNS/CNTs1 derived from the precursor with boric acid, urea and CNTs molar ratio of 2:4:1. Besides, the maximum absorption bandwidth (RL ≤ −10 dB) is as large as 4.0 GHz when the absorber thickness drops to 2.0 mm. More important, h -BNNS/CNTs1 has a low density of 112.6 ± 3.6 mg/cm 3, which is beneficial for practical applications. The significant enhancement in MA performance of h -BNNS/CNTs is mainly attributed to the improvement of impedance matching, interfacial polarization and multiple scattering after introduction of h -BNNSs.